(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The surge of Covid-19 pandemic placed the world in lockdown situation. The educational sector was badly affected by it. The schools, colleges and universities were closed the world over. In such situations, the teachers turned to online teaching mode to keep the education of students going. The sudden shift from face-to-face mode of teaching to online mode of teaching had put forth many problems and challenges before the teachers at each level of education. The present study aimed to explore the problems faced by the college teachers in online teaching of Samba district during the pandemic. Survey method was used to conduct the study. Self prepared questionnaire consisting of twelve closed ended questions and one open ended question was used to collect the data. College teachers of Samba district formed the population and forty teachers from five colleges of Samba district were randomly selected as a sample of the study. The data was analyzed using percentage. The paper highlights some of the problems faced by the teachers i.e. unfavorable home environment for online learning, lack of students interaction, lack of knowledge about online teaching technologies, poor network connection, Non Availability of smart phones with the students, lack of ICT tools with teachers, lack of internet access, power failure, high data cost, inequality issues and increased workload on teachers and technical glitch etc.. The paper also makes certain suggestions to address the issues and to be better prepared for future.